Economia da saúde: uma análise da produção científica no Brasil de 2014 a 2022 - Santos, Mirelly da Silva (Brasil, 2023)
The general objective of the research was to map the scientific production on health economics in the period from 2014 to 2022, in order to identify the main national journals that present publications on the subject. The following specific objectives are highlighted: a) To verify the number of articles published in the area of health economics; b) identify the journals that stand out in relation to the number of publications and present the Qualis of these journals; c) highlight the universities and/or institutions of origin of authors with articles published in health economics; and, d) present the thematic axes addressed in the analyzed articles. This is a descriptive study and secondary data from the Capes journal portal were used, considering Qualis from A1 to B4 in Economics, referring to the four-year period 2017 - 2020. It was observed that the selected articles fall mainly within the thematic axis of financing of actions and health services. As for institutions with greater participation in the authorship of publications in health economics, those located in the southeast region stand out, where most of the research groups in this area are located.